Ion solvation and association in LiClO4 – dimethylsulfoxide system - Gorobets, M.I.; Kirillov, S.A.; Gafurov, M.M.; Ataev, M.B.; Tretyakov, D.O. (Reports of the National Academy of Sciences of Ukraine, 2014)
Ionic equilibria in theLiClO4 – dimethylsulfoxide (DMSO) system at 90 ºC in a concentration range from 5 to 25% mole fractions of a salt have been investigated by means of Raman spectroscopy. Spectroscopic manifestations of hydrogen bonds between molecules of DMSO and ClO4− ions were detected. Concentrations of monomeric, dimeric, and solvating DMSO molecules; free solvent molecules and those included in the ClO4− ion solvation sphere; free anions, ion pairs, separated by a solvent, and contact ion pairs are identified. Conclusions have been made about the composition of all components of solutions.